The impact of electronic word-of-mouth (E-Wom) on purchase intentions during online shopping: Exploring E-Marketing In Pengkalan Chepa, Kelantan, Malaysia - Annrita Anushia Francis; Chew Yee Xain; Juliana Abd Kadir; Luqmanul Hakim Jamil (2023)
Electronic word-of-mouth (e-WOM) has become a significant emerging business strategy in the marketing and customer environments in the era of globalization. Due to technological advancements, one of the platforms for customers to express their views on products and services is electronic word-of-mouth, or e-WOM.Therefore, this study is to investigate the impact of electronic word of-mouth (e-WOM) on purchase intentions during online shopping. The Theory of Planned Behavior (TPB) was implemented in this study. This study was also conducted using a quantitative research approach, a Google Form questionnaire was distributed to 390 respondents in the Pengkalan Chepa region directly or via a link. The sampling technique used in this research is based on non-probability sampling which is known as convenience sampling. The Statistical Package for the Social Sciences (SPSS) was used to analyses the data collected. Several methodologies, including descriptive, reliability, and normality analysis, were used to analyses the collected data from the questionnaire. The results demonstrated that the independent variable (trust, attitude, perceived relevancy and quantity information) has a highly positive significant on the dependent variable of purchase intention. This study advances our knowledge of the still limited persuasive potential of digital communication. Additionally, it may help the community when establishing its own social media communication approach and enlighten businesses, especially Small and Medium-Sized Enterprises (SME), about the benefits of e- WOM adoption. This study offers suggestions to all aspects of society on how to use e-WOM to encourage people to engage in effective e marketing.